Phase-only array transmit beamforming without iterative/numerical optimization methods - Orlando, Danilo; Farina, Alfonso (Frontiers in Signal Processing, 2023)
In this letter, we address the problem of phase-only transmit beamforming to generate a wide beam with an almost flat mainlobe for phased arrays. Instead of resorting to time-demanding optimization procedures, the proposed method is grounded on the Fourier analysis and exploits the fact that radiation pattern can be written as the Fourier transform of the aperture illumination function. In this context, we consider a complex linear frequency modulated illumination function and derive the equations allowing for a control of the beam width. The related computational complexity is linear in the number of the array elements. The numerical examples show the effectiveness of the proposed method in forcing the desired beam shape with good sidelobes’ properties and also in comparison with an iterative competitor.